Analysis of neurite outgrowth activity of aqueous extract of Lignosus Rhinocerotis (COOKE) ryvarden in pc-12 cells / Eik Lee Fang - Eik, Lee Fang (2015)
Senescence of neuronal cells reduced the elongation and branching of axons. These lead to neurodegenerative diseases such as Alzheimer’s disease. Extracts of selected mushrooms used as folk medicines are being studied, Lignosus rhinocerotis (Cooke) Ryvarden, however has been singled out as one of the most potent mushroom with medicinal properties by communities in Malaysia. In this study, aqueous extract was extracted by boiling method mimicking the real cooking method. Activity of L. rhinocerotis aqueous extract in stimulating neurite outgrowth and the possible signalling pathway involved were investigated. Neurite outgrowth activity was assessed by number of neurite-bearing cells and immunoreactivity of neurons by indirect immunostaining with neurofilament protein. Aqueous extract of L. rhinocerotis gave the maximal stimulation for neurite outgrowth at a lower concentration of 20 μg/mL (w/v) when compared to H. erinaceus at 50 μg/mL (w/v) and T. heimii at 40 μg/mL (w/v). Lignosus rhinocerotis aqueous extract possessed NGF-like activity and up regulated ERK/MAPK signaling pathway for cell differentiation and cell growth.